Pengaruh Corporate Social Responsibility Terhadap Kinerja Inovasi UMKM Di Kecamatan Alok Timur - Maria Kristina Liu Wea; Wilhelmina Mitan; Pipit Niken Aurelia (Jurnal Riset Akuntansi, 2023)
This research aims to determine the influence of corporate social responsibility on the innovation performance of MSMEs in East Alok District. The method used in this research is a quantitative method. The population in this study were MSME actors in the Alok Timur District with a total of 1,548 MSME actors. The sampling technique used simple random sampling technique with a total sample of 94 respondents. In this study the types of data used are primary data and secondary data. The data collection procedure uses a questionnaire that is measured by a Likert scale. The data analysis technique used in this research uses a simple linear analysis method with descriptive statistical tests, data quality tests, classical assumption tests, and hypothesis tests. The research results show that partially corporate social responsibility has a positive effect on the innovation performance of MSMEs in East Alok District.